Line inductance stability operation domain assessment for weak grids with multiple constant power loads - Wang, Rui (2022)
Weak grids are gaining considerable attention since power generation resources are remote from constant power loads (CPLs), which results in low-frequency/harmonic oscillation. Meanwhile, due to the play, and plug demand of modern power system, the line inductance of weak grids often changes, which is also regarded as the variation regarding short circuit ratio (SCR). Based on this, the conventional impedance-based stability operation point assessment approaches should be expanded into stability domain assessment approach considering the line inductance variation. Therefore, the stability-oriented line inductance stability domain assessment approach for weak grids with CPLs is proposed in this paper. Firstly, the source impedance matrix of weak grid, and load admittance matrix of CPLs are separately built. Secondly, an improved stability forbidden domain criterion is proposed through related mapping transformation process, which has lower conservatism than two previous improved stability criteria. Thirdly, the improved stability forbidden domain criterion is switched into the condition that the intermediate matrices are Hurwitz. Meanwhile, the line inductance stability domain is directly obtained through these intermediate matrices, and guardian map theory. Finally, the simulation, and experiment results illustrate that the proposed approach has less conservatism, and high efficiency.